BUDAYA BERHUNI KAUM SUFISTIK BORJUIS: Kontestasi Simbolik dalam Konstruksi Rumah Adat Kudus - Said, Nur (UIN Maliki Malang, 2010)
Omah, Javanese term for house, is not only as a place to protect from hot and cold weather, importantly, as a place for Javanese people to actualize themselves both personally and socially. This is interesting to expose as its existence represents the symbolic fight of negotiation process between cultures happened in its period. The relationship between the house and its occupant symbolizes the cultural apprenticeship which is expressed in the use of the room. The house also represents the substance and material aspect, even the first one still becomes the main concern. The substance aspect can be seen in the ornament which sometimes still has animal picture, as Sunan Kudus is someone who has high tolerance. The material aspect expresses the strategy to defense the existence and dignity. As a whole, the house represents the face of Islam which is substantive-esoteric, and still considers existentialist-symbolic aspect as another important aspect.